2002
DOI: 10.1021/es011423j
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Oxidation of Bacteria, Bacterial and Fungal Spores, and Model Biofilm Components to Carbon Dioxide on Titanium Dioxide-Coated Surfaces

Abstract: We report carbon mass balance and kinetic data for the total oxidation of cells, spores, and biomolecules deposited on illuminated titanium dioxide surfaces in contact with air. Carbon dioxide formation by photocatalytic oxidation of methanol, glucose, Escherichia coli, Micrococcus luteus, Bacillus subtilis (cells and spores), Aspergillus niger spores, phosphatidylethanolamine, bovine serum albumin, and gum xanthan was determined as a function of time. The quantitative data provide mass balance and rate inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
154
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(159 citation statements)
references
References 21 publications
4
154
0
1
Order By: Relevance
“…When this damage reaches a level that cannot be repaired or reversed by the spores during germination, then the spore is inactive. Eventually, according to the results of Wolfrum et al [27], the spores could be completely mineralized. Considering the irradiation levels and the exposure times adopted in this work, mineralization is not expected to occur under our experimental conditions.…”
Section: Simplified Photocatalytic Inactivation Reaction Pathwaymentioning
confidence: 89%
See 1 more Smart Citation
“…When this damage reaches a level that cannot be repaired or reversed by the spores during germination, then the spore is inactive. Eventually, according to the results of Wolfrum et al [27], the spores could be completely mineralized. Considering the irradiation levels and the exposure times adopted in this work, mineralization is not expected to occur under our experimental conditions.…”
Section: Simplified Photocatalytic Inactivation Reaction Pathwaymentioning
confidence: 89%
“…Goswami et al [24] reported the total inactivation of Serratia marcescens in a photocatalytic reactor with recirculation. The photocatalytic inactivation of bioaerosols was also the subject of a handful of more recent publications [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. The use of photocatalytic process to degrade spores immobilized on a TiO 2 -coated surface was first reported by Wolfrum et al [27].…”
Section: Special Symbols [ ] Concentrationmentioning
confidence: 99%
“…TiO 2 morphology significantly affects its mobility inside a cell or through cell membranes, as well as the interactions with phagocytic cells that can trigger the signaling process for ROS generation [50]. The antimicrobial activity of nanoscale-TiO 2 towards Escherichia coli, Micrococcus luteus, Bacillus subtilis, and Aspergillus niger has been utilized in accelerated solar disinfection and in surface coatings [67,68,84].…”
Section: Toxicity Of Nanomaterialsmentioning
confidence: 99%
“…[4,50,53,67,84] Ultra-fine SiO 2 nanoparticles have been classified as human carcinogens [27]. Exposure to nano-sized SiO 2 causes alveolar cell toxicity and induces tumor necrosis genes in rats [3].…”
Section: Toxicity Of Nanomaterialsmentioning
confidence: 99%
“…For example, biocides containing heavy metal ions function by penetrating the cell wall and inhibiting the bacterium's metabolic enzymes, whereas antimicrobial agents with cationic surfaces cause rupture of the bacterium's cytoplasmic membrane. Examples of organic biocides include polymers, tertiary alkyl amines and organic acids [59,60], while inorganic biocides include silver, zinc oxide (ZnO), copper oxide (CuO), TiO 2 , and selenium [61][62][63][64][65][66]. Microcapsules containing biocides have also been developed in order to increase the longevity and efficiency of antimicrobial coatings [67][68][69].…”
Section: Antibacterial Coatingsmentioning
confidence: 99%